VIOLATIONS, POLITICS, AND THE APPLICABILITY OF INTERNATIONAL LAW: IS INTERNATIONAL LAW DEAD? - Agit Yogi Subandi; Isroni Muhammad Miraj Mirza; Rafika Rizky Aulia Rahman (PRANATA HUKUM, 2026)
The contemporary of international relations are increasingly marked by various violations and instances of non-compliance with international law, particularly by powerful states. This phenomenon has given rise to the perception that international law has lost its binding force or is no longer relevant. This article addresses two main issues: whether violations and non-compliance can be understood as signs of the “death” of international law from the perspective of Hans Kelsen’s theory of norms, and how the political nature of international law affects its applicability and function, particularly for Indonesia. This study employs a normative legal research method with a conceptual and analytical approach. The analysis is conducted using Hans Kelsen’s Pure Theory of Law as the primary framework, particularly regarding the distinction between fact (sein) and norm (sollen) as well as the concept of legal validity, which is then supplemented by critical and constructivist perspectives on the relationship between law, politics, and power. The research findings indicate that violations do not signify the absence or demise of international law. On the contrary of that, violations actually presuppose the existence of the violated norm and thus affirm the validity of international law as a normative order. Furthermore, the political nature of international law does not negate its legal character; rather, it shapes international law as a normative instrument used to legitimize, limit, and direct the exercise of power within the international community. For Indonesia, international law remains a vital instrument for advancing national interests and building legitimacy within a global order that is not entirely equitable.